DESPICABLE ME. 2 - Renaud, Chris; Coffin, Pierre; Meledandri, Chris; Healy, Janet; Paul, Cinco; Daurio, Ken; Carell, Steve; Wiig, Kristen; Bratt, Benjamin; Cosgrove, Miranda; Brand, Russell; Jeong, Ken ([California] : Universal Studios, 2013)
This blockbuster animated comedy from Illumination Entertainment sees the return of former super-villain Gru, who has retired from a life of crime to raise his three daughters. But things take an unexpected turn when he is recruited by the Anti-Villain League to track down an elusive criminal who is threatening the world. Now, with new partner Lucy Wilde by his side, Gru and the Minions set off on an unpredictable and unexpected adventure.
1080p high definition widescreen 1.85:1.
Original songs and themes by Pharrell Williams ; score by Heitor Pereira ; editor Gregory Perler ; production designers Yarrow Cheney, Eric Guillon.
Steve Carell, Kristen Wiig, Benjamin Bratt, Miranda Cosgrove, Russell Brand, Ken Jeong.
U (General).
Blu-ray disc.
In English, Russian, Thai, Cantonese, Mandarin ; with subtitles: English SDH, Cantonese, Russian, Thai and traditional Mandarin.
Keywords: Supervillains -- Drama; Orphans -- Drama; Animated films; Action and adventure films